Who are good home-based care volunteers? - G. Marincowitz; C. Jackson; G.S. Fehrsen (South African Family Practice)
Aim: The aim of the study was to describe the characteristics of volunteers who remained active in the home-based care project located in Tzaneen (Limpopo Province) and thereby assist the project leaders to improve the recruitment and quality of the service in the future.